2006
DOI: 10.1103/physrevlett.97.255902
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Mechanism of Boron Diffusion in Silicon

Abstract: B diffuses in crystalline Si by reacting with a Si self-interstitial (I) with a frequency g and so forming a fast migrating BI complex that can migrate for an average length lambda. We experimentally demonstrate that both g and lambda strongly depend on the free hole concentration p. At low p, g has a constant trend and lambda increases with p, while at high p, g has a superlinear trend and lambda decreases with p. This demonstrates that BI forms in the two regimes by interaction with neutral and double positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 25 publications
4
31
0
Order By: Relevance
“…In this scenario B, that is the most used p-type dopant in Ge as in Si, seems to show a quite anomalous behavior in Ge. The dominance of interstitials in the B diffusion in Si is well established from different studies [1,7], and this behavior is confirmed also for B in Si-Ge alloys up to 20% Ge contents [8]. In spite of this, there are only a few studies on B diffusion in pure Ge.…”
Section: Introductionsupporting
confidence: 54%
“…In this scenario B, that is the most used p-type dopant in Ge as in Si, seems to show a quite anomalous behavior in Ge. The dominance of interstitials in the B diffusion in Si is well established from different studies [1,7], and this behavior is confirmed also for B in Si-Ge alloys up to 20% Ge contents [8]. In spite of this, there are only a few studies on B diffusion in pure Ge.…”
Section: Introductionsupporting
confidence: 54%
“…In order to quantitatively study the self-interstitial supersaturation, we fitted the B profiles by means of a χ 2 optimization of numerical simulations based on the g-λ diffusion model, 20,24,36 successfully applied also for B diffusion in Ge. 16,19 Here, g gives the B-self-interstitial interaction rate leading to one B diffusion event, while λ is the mean length of 43 and 44)], but the equilibrium self-interstitial density in Si is much larger than in Ge, weakening the effect of self-interstitial injection during OED in Si.…”
Section: Resultsmentioning
confidence: 99%
“…19. SIMS analyses were used to measure B diffusion, whose simulation based on the model of Cowern et al 20,24,36 allows evidence of changes of self-interstitial density in Ge. 3,16,19,37 Figure 3 shows the B profiles of the MBE-Ge after implantation (dashed line) and after annealing at 650…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…66 First, boron profiling with secondary ion mass spectrometry (SIMS) has been developed with high accuracy and sensitivity. The improvement of the technique consisted in cooling the samples at À70 C, in order to suppress the long-range anomalous diffusion of B occurring at room temperature during the analysis and thus distorting the profiles, 67 and in flooding the samples with oxygen during the analysis, for enhancing the measurement sensitivity by a factor of 20.…”
Section: B Atomistic Pathways Of B Diffusionmentioning
confidence: 99%